SURVIVAL ANALYSIS AMONG VERY OLD MEXICAN AMERICAN: THE IMPORTANCE OF IMMIGRATION. (11th November 2018) - Emerson, K; Dave, I; Huang, H
Abstract: The older Hispanic population is growing rapidly in the United States. Research consistently shows a survival advantage among Hispanics, despite a worse risk profile (i.e. Hispanic Paradox). The goal of this study was to confirm this survival advantage among very old Mexican Americans (75+) and to test the impact of immigration status on mortality risk. We used data from the 1993–1994 Hispanic Established Population for the Epidemiological Study of the Elderly (Hispanic EPESE), which was linked to follow up vital status in 2016. We used Cox proportional hazards models to estimate risk of death for those born in the US (vs. foreign-born), while controlling for demographics and health conditions. The sample (n=1, 108) was a majority female (59%), non-married (58%), and had an average education of 3.33 years. The average age was 80.91 (range 75–105). The multivariate Cox regression model showed that US-born Hispanic elders had 26% higher odds of death compared to foreign born (p-value =.00015). The models controlled for demographics and health conditions. While being female was a significant direct predictor of survival, the immigration effect did not differ by gender. These results confirm that a significant factor influencing survival among very older Mexican Americans is immigration status. This suggests that the healthy immigrant effect maintains even in old age. Policy and practice implications will be discussed.